Personal Hygiene Practices among Selected Rural School Children in Bangladesh (Delta Medical College Journal, 2022)
Background: Proper hygiene practices play vital roles in prevention of communicable diseases and maintenance of health for children in developing countries.Objective: To assess the status of personal hygiene practices among the rural school children.Materials and method: This cross-sectional descriptive study was conducted from January to June 2014 among the children of class VIII, IX and X of Defalbari and Nagarbathan high school of Jhenaidah district, Bangladesh. A total of 240 children were selected through purposive sampling and data were collected through face to face interview with a pretested semi-structured questionnaire.Results: Total 240 students’ mean age was 15.36±1.69 years and 56.3% was boy. About 52.5% of the students’ monthly family income was below 10,000 taka, 42.5% were living in kacha house. About 77.1% students practiced hand washing before meal and 73.3% after using toilet. About 47.5% students had sanitary latrine in their home and 56.2% had practices of wearing shoes in toilet. About 72.9% students had daily bathing practices and 39.6% students trimmed their nail weekly. Students’ mothers’ education status had significant association with hand washing practices both before meal and after using toilet.Conclusion: Proper practices of personal hygiene keep young children away from many diseases and help in maintaining growth and development. Mothers’ education status was found to have significant association with students’ personal hygiene practices. So, effort should be made to aware every school going children and their parents about the benefits of regular practice of personal hygiene for a bright and healthy life.Delta Med Col J. Jul 2020 8(1): 28-31